(untitled) (Journal of the College of Basic Education, 2024)
The thesis aimed to prepare educational units using the strategy of overlapping waves with hyper-overlapping media in learning to dribble in soccer for students, and to identify the effect of the strategy of overlapping waves with hyper-overlapping media in learning to dribble in soccer for students, and to identify the preference of the experimental and control research groups in learning to dribble in soccer for students. The researcher used the experimental method due to its suitability to the nature of the problem, and the experimental method determined the research population in an intentional manner from the students of the second intermediate grade in Al-Mufid Secondary School for Boys in the Anbar Education Directorate - Fallujah Department for the academic year 2023/2024, and they numbered (102) students divided into three academic divisions. Section A is 34, Section B is 35, Section C is 33, and as for the research sample, the research sample was chosen in a systematic random way (lottery), as the research sample consisted of (45) students who were divided into three groups of equal number and with ( 15) students for each group, one of which is a control group and the other two are a first experimental group and a second experimental group, with a percentage of (44.12%) from the original research population. 10 students were approved for the exploratory experiment from Division C. The rest of the students are enrolled in the physical education lesson on football, but the researcher does not deal with With them statistically. One of the most important research procedures was that the researcher conducted an equivalence test for the three research groups, after which the researcher prepared educational units for the two experimental groups, the first using the overlapping waves strategy using super-overlapping media, and the second experimental group using the overlapping waves strategy. As for the group, it remained in the method used by the teacher. The researcher prepared 20 educational units, each 45 minutes long and no. Two educational units per week, and the total time was 900 minutes. After that, the post-test was conducted, and the researcher relied on appropriate statistical methods to reach the most important results that led the researcher to conclusions, the most important of which is the first experimental group, according to the strategy of overlapping waves using super-overlapping media, which had the greatest effect on the skill of dribbling in football. The experimental group. The second was based on the strategy of overlapping waves, which had less effect than the first experimental group. The recommendations included an emphasis on adopting the strategy of overlapping waves using super-overlapping media as an effective means to enhance dribbling in football. Special attention should be given to the strategy of overlapping waves using super-overlapping media to develop the skills of players in football. Emphasis was placed on The importance of adopting interactive and gradual learning strategies, such as overlapping waves, in concretely enhancing the process of learning football skills.